CRYPTOCURRENCY PHENOMENON IN THE INTERNATIONAL MONETARY SYSTEM (Economics and region, 2017)
UDC 336.74 Vasylenko Artur, post-graduate student. Mariupol State University. Cryptocurrency Phenomenon in the International Monetary System. The main prerequisites of cryptocurrency emergence in the international monetary system in terms of regionalization of the world economy are defined in the article. Determination of «cryptocurrency» category was analysed from the point of two main approaches to its treatment: on the one hand cryptocurrency is admitted to be the currency equally to the sovereign currency, and on the other hand it is considered as an unrecognized virtual asset.The main consequences which arise in case of widespread use of crypto currency for the country and for the parties that agreed to use cryptocurrency were analysed and systematized.On the basis of the research, given the current trends in the world economy, the author put forward and substantiated the hypothesis to classify the phenomenon of cryptocurrency as the effects of a famous philosophical «Negation of negation law» formulated by G. Hegel at the beginning of the XIX century. Keywords: cryptocurrency, material money, electronic money, digital currency, regional currency integration, blockchain, mining, capitalization, «Negation of negation law».